EVELYN’S ARCHETYPES IN REID’S THE SEVEN HUSBANDS OF EVELYN HUGO - Prameswari, Ratri Candra (Universitas Negeri Surabaya, 2025)
Personality is inherently adaptive, often shifting in response to environmental demands to meet expectations, gain recognition, and ensure survival. This concept is illustrated through the character of Evelyn Hugo, a Hollywood actress whose life is fraught with drama and controversy, in Taylor Jenkins Reid’s The Seven Husbands of Evelyn Hugo. This study adopts a psychoanalytic approach grounded in Carl Jung’s theory of the collective unconscious to examine how archetypes are represented in Evelyn’s character. It further investigates the extent to which her past experiences shape the emergence of these archetypes. The analysis draws upon selected dialogues, monologues, and narrative elements that align with the study’s objectives. The findings reveal that Evelyn’s personality is expressed through four major Jungian archetypes: persona, shadow, animus, and self, all of which are significantly influenced by her psychological trauma and formative life experiences.